A review of anomalous origination of a coronary artery from an opposite sinus of Valsalva (ACAOS) impact on major adverse cardiovascular events based on coronary computerized tomography angiography: a 6-year single center review. (December 2014) - Clark, Richard A.; Marler, Adam T.; Lin, Charles K.; McDonough, Ryan J.; Prentice, Ryan L.; Malik, Jamil A.; Villines, Todd C.; Hulten, Edward A.; Thomas, Dustin M.; Slim, Ahmad M.
Background: Anomalous origination of a coronary artery from an opposite sinus of Valsalva (ACAOS) is a rare finding that is typically found on autopsy in a person with sudden cardiac death or during routine cardiovascular testing. The true prevalence is unknown for this reason. There is also question to the specific anatomy of the anomalies themselves and how best to correct them. Methods: We performed a retrospective chart review of all coronary computed tomography angiography (CCTA) studies to evaluate the incidence of all-cause mortality, nonfatal myocardial infarction, stroke and late revascularization (>90 days following CCTA) from January 2005 until July 2012. We describe the origin of the artery, its course, slit-like appearance and treatment in this population. Results: We reviewed 1518 CCTA reports and identified 22 patients with ACAOS with an incidence of 1.4% of our original study population over a review period of 6 years with a resultant median follow-up period of 25 months [interquartile range (IQR)25, 75 12–34 months]. The indication for CCTA was for chest pain in the majority of patients (73%). We had one patient undergo surgical repair and one with coronary bypass grafting for unrelated symptomatic coronary artery disease. Conclusion: ACAOS continues to be a rare but presumed fatal condition in subsets identified to carry high risk features. As the characteristics of the anomalous vessels that increase risk are still debated, over an intermediate to long follow up in a single large center, none of the different anomalous findings with varying degrees of high risk findings were associated with sudden death.